Implementation of IoT and Blockchain for Halal Product Traceability in Global Supply Chains - Muammar Rinaldi; Sattar Rasul (International Journal For Advanced Research, 2026)
The global halal supply chain encountered significant transparency challenges and fragmented information sharing across international borders. This research developed an integrated traceability system utilizing Internet of Things sensors and a permissioned Blockchain architecture to ensure the religious integrity of products. The study followed the Design Science Research methodology, simulating the logistics of protein-based products across multiple global stakeholders with three hundred network nodes. Results demonstrated that the integrated system achieved a throughput of three hundred fifty transactions per second with a latency of less than two seconds. Sensor data provided real-time monitoring of environmental conditions with a ninety-nine point eight percent accuracy rate in detecting unauthorized deviations. The implementation reduced the total time required for end-to-end traceability from seven days to less than thirty minutes, leading to an eighty-five percent reduction in administrative paperwork. Stakeholder evaluations indicated an eighty-nine percent increase in consumer trust towards the digitalized halal certification. The study concluded that the synergy between the Internet of Things and Blockchain established a reliable "Halal by Design" framework that automated compliance through smart contracts. Although financial barriers for small and medium enterprises persisted, the system provided a scalable solution for maintaining religious and operational integrity in global markets. This innovation offered significant contributions to the digital transformation of the Sharia economy.